2021
DOI: 10.1038/s41416-021-01599-0
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a cGAS-STING-mediated immune response predicts response to neoadjuvant chemotherapy in early breast cancer

Abstract: Background The DNA-damage immune-response (DDIR) signature is an immune-driven gene expression signature retrospectively validated as predicting response to anthracycline-based therapy. This feasibility study prospectively evaluates the use of this assay to predict neoadjuvant chemotherapy response in early breast cancer. Methods This feasibility study assessed the integration of a novel biomarker into clinical workflows. Tumour samples were collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…Our findings are timely given the active clinical development of STING agonists as a promising new class of cancer immunotherapeutics [ 24 ]. Activation of the cGAS-STING immune sensing pathway is a validated strategy to increase tumor immunogenicity and improve antitumor efficacy in preclinical and clinical studies [ 56 , 57 ]. Natural STING ligands, including cGAMP, provide proof of principle that STING activation can promote antitumor efficacy, but these ligands suffer from poor cell penetration and metabolic liabilities [ 11 , 58 , 59 ] that necessitate intratumoral injections and are not maximally effective against all of the common variants of human STING [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are timely given the active clinical development of STING agonists as a promising new class of cancer immunotherapeutics [ 24 ]. Activation of the cGAS-STING immune sensing pathway is a validated strategy to increase tumor immunogenicity and improve antitumor efficacy in preclinical and clinical studies [ 56 , 57 ]. Natural STING ligands, including cGAMP, provide proof of principle that STING activation can promote antitumor efficacy, but these ligands suffer from poor cell penetration and metabolic liabilities [ 11 , 58 , 59 ] that necessitate intratumoral injections and are not maximally effective against all of the common variants of human STING [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The immune score as well as some immune-associated genes such as chemokines, cytokines, immune regulators, and human leukocyte antigens were significantly higher in the anthracycline-S group. Previous studies reported that anthracycline-based chemotherapy was known to induce cytotoxic T cell proliferation and enhance the anti-tumor immune response by turning a “cold” tumor into a “hot” one [ 3 , 28 ].Besides, several studies suggested that the combination of anthracycline and immune checkpoint inhibitors might improve survival [ 29 , 30 , 31 ]. Our results suggested that anti-tumor-associated immunological processes were much more active in the anthracycline-S group than in the anthracycline-R group and that the anthracycline-R samples exhibit restricted anti-tumor immunity from the very beginning of anthracycline treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Nottingham histological grade of TCGA was manually calculated from pathology reports of TCGA-BRCA as previously reported [ 33 ]. We also downloaded the following curated RNA-seq data of the bulk tumors from GEO database: GSE12276 ( n = 195) [ 34 ] of early breast cancer with known later metastatic sites, GSE124647 ( n = 140) [ 35 ] and GSE159956 ( n = 295) [ 36 ] of advanced breast cancer, GSE110590 ( n = 77) [ 37 ] of primary and metastatic samples of advanced breast cancer, and GSE180280 ( n = 37) [ 38 ], GSE87455 ( n = 153) [ 39 , 40 , 41 ], GSE28844 ( n = 61) [ 42 ], GSE21974 ( n = 57) [ 43 ] as cohorts including before and after neoadjuvant chemotherapy samples of primary breast cancer. Matching probes were used for NR2F1 expression, and the average of the probes was used when there were multiple probes.…”
Section: Methodsmentioning
confidence: 99%